Lurasidone‐induced hyperosmolar hyperglycemic syndrome: A case report. Issue 3 (24th May 2022) - Hanyu, Shota; Kojima, Yusuke; Murai, Toshiya; Kawashima, Hirotsugu
Abstract: Introduction: Lurasidone has few metabolic adverse effects and is recommended as an alternative when other antipsychotic drugs considerably increase body weight or blood sugar concentrations. Case presentation: An 81‐year‐old man with bipolar disorder developed hyperosmolar hyperglycemic syndrome as a side effect of lurasidone. Routine monitoring of blood glucose concentrations led to the early detection and treatment of this disease, preventing life‐threatening complications. Discussion and conclusion: We describe a rare case of lurasidone‐induced hyperosmolar hyperglycemic syndrome. The mortality rate of this syndrome is estimated to be up to 20%. This rate is significantly higher than that of diabetic ketoacidosis (currently <2%). Although lurasidone is considered to have a low risk of raising blood glucose concentrations, symptoms of hyperglycemia must be evaluated and blood glucose concentrations should be monitored regularly.